2008
DOI: 10.1182/blood-2007-10-116111
|View full text |Cite
|
Sign up to set email alerts
|

Levo- but not dextro-1-methyl tryptophan abrogates the IDO activity of human dendritic cells

Abstract: IntroductionIDO is an enzyme that catabolizes tryptophan and was shown to protect the fetus from rejection mediated by maternal T cells. 1 Such a basic mechanism that evolved for the perpetuation of species might be expected to be used for the regulation of other biologic processes. Researchers were therefore motivated to look for a role of IDO in the regulation of immune responses in health and disease. An objective that has challenged the scientific community for decades is the unraveling of immunologic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(140 citation statements)
references
References 16 publications
7
129
3
1
Order By: Relevance
“…Selectivity for IDO1 relative to tryptophan 2, 3-dioxygenase (TDO) (EC 50 TDO: EC 50 IDO1) was 180. These efficacy and selectivity estimates for IDOInh are higher than those reported for 1-methyltryptophan (Hou et al, 2007;Lob et al, 2014), the IDO inhibitor used to-date to study effects of KYN-pathway inhibition (Dobos et al, 2012;Kiank et al, 2010;O'Connor et al, 2009b Naive mice were allocated randomly to four treatment groups: IgG2a-Vehicle (IgG2a-VEH, N=7), IgG2a-IDO inhibitor (IgG2a-IDOInh, N=8), CD40AB-VEH (N=7) and CD40AB-IDOInh (N=8).…”
Section: Cd40ab  Ido Inhibitor On Saccharin Drinking and Levels Of Ccontrasting
confidence: 40%
“…Selectivity for IDO1 relative to tryptophan 2, 3-dioxygenase (TDO) (EC 50 TDO: EC 50 IDO1) was 180. These efficacy and selectivity estimates for IDOInh are higher than those reported for 1-methyltryptophan (Hou et al, 2007;Lob et al, 2014), the IDO inhibitor used to-date to study effects of KYN-pathway inhibition (Dobos et al, 2012;Kiank et al, 2010;O'Connor et al, 2009b Naive mice were allocated randomly to four treatment groups: IgG2a-Vehicle (IgG2a-VEH, N=7), IgG2a-IDO inhibitor (IgG2a-IDOInh, N=8), CD40AB-VEH (N=7) and CD40AB-IDOInh (N=8).…”
Section: Cd40ab  Ido Inhibitor On Saccharin Drinking and Levels Of Ccontrasting
confidence: 40%
“…S3B). This activity was blocked by 1-methyl-L-tryptophan, a known IDO1 inhibitor, and not by its enantiomer 1-methyl-D-tryptophan, confirming the lack of inhibition of IDO1 by the latter (37,38). When we added mature-DC conditioned medium to CD4 þ T cells activated with coated anti-CD3 antibody, we observed that T-cell proliferation was prevented, whereas it was maintained with the immature DC-conditioned medium (Supplementary Fig.…”
Section: Characterization Of Ido1-positive Cells In Tdlnsmentioning
confidence: 59%
“…Data reported for D-1MT, a described IDO2 inhibitor currently in clinical development, indicate that there was no decrease in plasma kynurenine levels in nonhuman primates (24) or in patients in early clinical trials (27). Multiple groups have described differences between D-1MT and L-1MT, showing that it is, in fact, L-1MT that can both decrease kynurenine generation and restore impaired proliferation of several T cell subsets and that IDO1 drives tryptophan catabolism in human dendritic cells (28,29). Hydroxyamidines, active against IDO1, suppress kynurenine generation in cells and in vivo and are therefore suitable to test the hypothesis that IDO1 inhibition may provide clinical benefit to cancer patients.…”
Section: Discussionmentioning
confidence: 99%